Optimizing the utilization of soybean and benniseed (in poultry feeds) through dietary supplementation with microbial phytase (2006)
The effects of microbial phytase (Natuphos® 5000) supplementation of corn-soybean and benniseed based diets were studied with two weeks old broiler birds on the parameters of growth performance, nutrient retention, and amino acid digestibility. One hundred and twenty chickens within a weight range of 190 to 210g were allotted in a completely randomised 2 x3 factorial arrangement to six dietary treatments. Body weight gain (g) 1074.17 + 12.26, feed intake (g) 1913.17 ± 15.60 and protein efficiency ratio 2.54 ± 0.16 were significantly (p '< 0.05) increased by phytase supplementation of soybean meal and benniseed diets. Significant (p •: 0.05) increases were also obtained for apparent retentions of dry matter (DM) 68.68 ± 3.72, nitrogen (N) 56.21 ± 2.83, phosphorus (P) 39.00 ± 2.14 and calcium (Ca) 58.78 ± 3.16 and apparent faecal digestibilities of protein (%) 8.11 ± 56 and amino acids. There were however significant (P • 0.05) differences in the magnitude of response by soybean meal and benniseed to phytase supplementation. For soybean meal diets, apparent retentions of N 55.74 ± 2.83 and p 37.88 ± 2.14 and protein digestibility 00.36 ± 1.20 increased-rapidly (p ■ 0.05) with 400 FTU/kg phytase but marginally with 800 FTU/kg phytase. On the contrary for benniseed diets, supplementation with 400 FTU/kg phytase increased amino acid digestibility marginally while 800 FTU/kg phytase significantly (p < 0.05) increased the digestibility of all amino acids.